REDESIGNING JUSTICE FOR PLURAL SOCIETIES ([S.l.])
1 online resource
Keywords: This volume examines cases of accommodation and recognition of minority practices: cultural, religious, ethnic, linguistic or otherwise, under state law. The collection presents selected situations and experiences from a variety of regions and from different legal traditions around the world in which diverse societal stakeholders and political actors have engaged in processes leading to the elaboration of creative, innovative and, to a certain extent, sustainable solutions via accommodative laws or practices. Representing multiple disciplines and methodologies and written by esteemed scholars, the work analyses the pitfalls and successes of such accommodative practices, presenting insights into how solutions could or could not be achieved. The chapters address the sustainability and transferability of such solutions in order to further the dialogue in both scholarly and policy spheres. The book will be essential reading for academics, researchers, and policy-makers in the areas of minority rights, legal anthropology, law and religion, legal philosophy, and law and migration.